Detection of urinary Chlamydia trachomatis, Mycoplasma genitalium and human papilloma virus in the first trimester of pregnancy by PCR method - Monireh Rahimkhani; A. Mordadi; M. Gilanpour (BMC, 2018)
Abstract Background Miscarriage and preterm delivery are the most important challenges of pregnancy. Different bacterial and viral infection may cause miscarriage and preterm delivery. Among bacterial factors, Mycoplasma genitalium and Chlamydia trachomatis have the most important role and human papilloma virus (HPV) is the leading viral factor in this regard. Methods First void urine samples were collected from 119 pregnant women who visited health centers for routine first-trimester screening (12-14 weeks gestation). About 10 ml of the sample was centrifuged at 3000×g for 20 min and 1-2 ml of the sediment was transferred to sterile microfuges and stored at − 20 °C until analysis. DNA extraction was conducted using A101211 kits imported by Pars Tous Biotechnology Company. The following commercial kits, imported by Pars Tous Biotechnology, were used for PCR. Results There is no significant association between urinary isolation of C. trachomatis and miscarriage (P = 0.93) and there is no significant association between urinary isolation of M. genitalium and miscarriage (P = 0.80). Regarding HPV, since all urine samples were PCR-negative, comparison was not possible. C. trachomatis was isolated from the urine samples of 6.72% of the pregnant women who underwent first-trimester screening in health centers using PCR. Previous studies reported a mean chlamydia isolation rate of 3% from urine specimens collected from pregnant women in general. T test showed no significant difference between the two groups (P = 0.10). Based on present study the mycoplasma isolation rate was 17.65% using PCR. Previous studies reported a mean mycoplasma isolation rate of 10% from urine specimens collected from pregnant women in general. T-test showed a significant difference between the two groups (P = 0.03). Discussion First void urine samples in pregnant women may be an appropriate sample for detection of C. trachomatis and M. genitalium; however, it is not a good method for HPV isolation therefore vaginal or cervical discharge specimens should be used instead for detection of HPV.